2017
DOI: 10.1080/1354750x.2017.1387935
|View full text |Cite
|
Sign up to set email alerts
|

Biological monitoring of exposure to low concentrations of benzene in workers at a metallurgical coke production plant: new insights into S-phenylmercapturic acid and urinary benzene

Abstract: SPMA and U-Ben at the next BS were dependent on the exposure to low benzene concentrations suffered in the previous work shift, prompting a reconsideration of the urine sampling time recommended by the American Conference Governmental Industrial Hygienists (ACGIH).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…It is noteworthy to mention, though, that the values reported were surprisingly high (median levels of 2.14 and 5.30 µg/g creatinine for SPMA and SBMA, respectively) and this might be due to the presence of tobacco smokers among study subjects, which was not controlled [31]. Lovreglio and co-workers, assessing SPMA levels, revealed that coke oven workers were exposed to a low level of benzene and reported a median level of SPMA in the end-shift urine equal to 0.50 µg/g creatinine (from 0.10 to 6.89 µg/g creatinine); they also reported higher concentrations in oven standpipe workers than in byproduct workers [28]. Previous studies reported urinary levels of SPMA from 3.16 to 34.53 µmol/mol creatinine (6.68-72.96 µg/g creatinine) [32], from 0.4 to 62.6 µmol/mol creatinine (0.85-132.3 µg/g creatinine) [33], from 0.40 to 38.56 µg/g creatinine [29], and from <0.3 to 1020 µg/g creatinine [30].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It is noteworthy to mention, though, that the values reported were surprisingly high (median levels of 2.14 and 5.30 µg/g creatinine for SPMA and SBMA, respectively) and this might be due to the presence of tobacco smokers among study subjects, which was not controlled [31]. Lovreglio and co-workers, assessing SPMA levels, revealed that coke oven workers were exposed to a low level of benzene and reported a median level of SPMA in the end-shift urine equal to 0.50 µg/g creatinine (from 0.10 to 6.89 µg/g creatinine); they also reported higher concentrations in oven standpipe workers than in byproduct workers [28]. Previous studies reported urinary levels of SPMA from 3.16 to 34.53 µmol/mol creatinine (6.68-72.96 µg/g creatinine) [32], from 0.4 to 62.6 µmol/mol creatinine (0.85-132.3 µg/g creatinine) [33], from 0.40 to 38.56 µg/g creatinine [29], and from <0.3 to 1020 µg/g creatinine [30].…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, coke oven workers might also be exposed to VOCs emitted during destructive distillation. Indeed, a certain number of studies assessed the exposure to VOCs in coke oven workers quantifying their levels in workplace and breathing zone air, with overall levels ranging from 22.6 µg/m 3 to 2.17 mg/m 3 [20][21][22][23][24][25][26][27][28]. Only a few studies performed biomonitoring of VOC metabolites in coke oven workers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The substance chosen as a biomarker of exposure to a given xenobiotic should be easy to extract from the biological material and should show, in analysis, significant correlation with the size of the absorbed dose of xenobiotic. The biological monitoring is the study of the concentration of the toxic substance or metabolite produced by the action of biological material [ 6 , 7 , 8 ]. Knowing the path and speed of change that various substances in the body are subjected to, based on the analysis of biomarkers of exposure, one can assess the size of the absorbed dose of xenobiotic and the resulting health risks.…”
Section: Introductionmentioning
confidence: 99%
“…They are not evenly distributed in plants; usually, they accumulate in their action place. Therefore, herbicide residues in plants are also not evenly distributed [ 8 , 19 , 20 ]. The residues in food products of active substances of herbicides used in plant production may be significant risk factors for lipid metabolism disorders, such as increased levels of triglycerides, total cholesterol, and low-density lipoprotein (LDL) fraction; lowering the level of lipoproteins in the blood; blood density (HDL), which leads to an increase in atherosclerotic changes in the aorta and coronary arteries; and diseases of the cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%